Asperger’s Disorder and Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs)
Five boys with both Asperger’s disorder and Tourette syndrome, exceptional verbal intelligence, and clumsiness presented with peer-related social difficulties and a flapping stereotypy in a report from New York University Medical Center.